Transition of land use/cover in world heritage cities under climate crisis - Yinshuai Li; Nan Jia; Chenglong Yin; Ruishan Chen (Ecological Indicators, 2024)
World Heritage Cities (WHCs) contain profound historical legacies and distinctive architectural styles. However, climate change significantly influences land use/cover (LUC) patterns, with both direct and indirect implications for the preservation of cultural heritage integrity and authenticity, as well as for urban sustainability. This study focused on WHCs identified as climate disadvantages by the ND-GAIN Country Index. We employed transfer matrices and dynamic degree models to analyze the spatial and temporal dynamics of LUC over four periods (2000–2005, 2005–2010, 2010–2015, and 2015–2020). Furthermore, intensity map was utilized to comprehensively analyze the transition tendencies, including inflows and outflows, absolute and relative intensities, and their impacts on LUC structures. The results reveal the following key findings: (1) Between 2000 and 2020, 20 WHCs with climate disadvantages are primarily located in South America, Africa, and Asia. (2) Bare areas constitute the dominant land cover (51.40% to 52.82%), while impervious surfaces are less and scattered (0.15% to 0.25%). (3) Although some bare areas tend to be outflowed as sparse vegetation, the degree of “greening” remained insufficient. The transition from grassland to sparse vegetation displays a systematic tendency, highlighting the risk of continuous degradation. (4) Instances of “counter-urbanization”, where impervious surfaces transition into rain-fed and irrigated croplands, has minimal impact on overall urbanization trends. (5) Forests exhibit complex and dynamic interconversions, while wetlands and irrigated cropland tend to degrade into bare areas and rain-fed cropland, indicating an increasing risk of aridification. This study provides effective data support to enhance the understanding of how climate change affects LUC in WHCs, contributing to formulating more sustainable urban planning and land management policies and maintaining the preservation and protection of world heritages.